Arterial injury and pseudoaneurysm formation after lesser trochanter fracture. (2015) - Regus, Susanne; Lang, Werner
Highlights: We report a false aneurysm of the deep femoral artery after uneventful stabilization of a hip fracture. Plain X-ray showed displaced lesser trochanter in close proximity to the deep femoral artery as this was calcified. CT scan confirmed an arterial lesion due to displaced lesser trochanter. The bony spike was removed surgically and the deep femoral artery was repaired using a vein patch. Abstract: Introduction: Vascular complications after hip fracture are rare but can be life-threatening, especially in the elderly and if diagnosed late. Presentation of the case: We report a false aneurysm of the calcified deep femoral artery after hip fracture and uneventful stabilization with a gamma nail, in an 85 year old woman. Three weeks after surgery there was swelling of the proximal thigh. Ultrasound scan revealed a false aneurysm of the deep femoral artery and plain X-ray showed a lesser trochanter fragment spiking the calcified deep femoral artery. Open repair of the pseudo-aneurysm with a vein patch was performed. Discussion: Nowadays the preferred imaging of false aneurysms is by computed tomographic (CT) angiography but this involves high radiation and nephrotoxic contrast agents and may delay diagnosis. What made this a special case was the post-operative plain X-ray which showed a displaced fragment of the lesser trochanter spiking the calcified deep femoral artery, as confirmed on CT scanning. Conclusion: Surgeons should pay attention to any displaced bone fragments close to calcified vessels, especially in the evaluation of routine x-rays following surgical treatment of fractures. This could minimize the potential life-threatening risk of delayed diagnosis, especially because it represents a routine image following surgical fracture treatments.